Freeware e-Class untuk Memudahkan Siapa Saja Mengklasifikasi dan Memahami Sistem Klasifikasi Berbasis DDC - Rotmianto Mohamad (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2019)
Various definitions of classification were put forward by many experts. But most of all, classification is a system for organizing knowledge (for organizing knowledge). Likewise, with the DDC-based classification, there have been various applications both free and paid. In this writing only will be discussed about e-Class or Electronic Classification. The existence of e-DDC and e-Class is also very suitable for all types of libraries starting from school libraries, public libraries, special libraries, even college libraries, especially its free nature.